Exploring the views and experiences of frailty and resilience among people experiencing homelessness in Ireland: A qualitative study - Thomas Cronin; Susan M. Smith; John Travers (PLoS ONE, 2026)
Background People experiencing homelessness (PEH) have high levels of frailty. However, their views on frailty, resilience, and the broader contextual factors that shape these experiences remain underexplored. Method This was a qualitative study involving semi-structured interviews with 25 participants recruited from a primary care-based feasibility trial. Participants in the trial were adults aged 18 years and older with pre-frailty and frailty who were homeless. A convenience sampling strategy was used, with only participants who completed in-person follow-up invited to participate. Interviews were analysed thematically using Braun and Clarke’s framework. The COREQ checklist guided study reporting. Results Three main themes were identified from the data: (1) Frailty and homelessness – how homelessness both contributes to and magnifies frailty; (2) Survival – building resilience of PEH through coping mechanisms and informal support; and (3) Systemic neglect – the structural barriers and inadequate supports encountered by PEH. Conclusions Frailty was experienced by participants as a multidimensional challenge, shaped by the realities of homelessness. Mental health was frequently described as central to the experience of frailty and should be prioritised in service responses. Addressing frailty in this population requires holistic approaches that consider structural disadvantage and the psychosocial context, alongside physical interventions.